Soil erosion studies under simulated rainfall conditions in a lateritic terrain - Praveena K K (Department of Land and Water Resources and Conservation Engineering, Kelappaji College of Agricultural Engineering and Technology, 2014)
Soil erosion IS a complex phenomenon involving the detachment and transport of soil particles, storage and runoff of rainwater and infiltration. Soil erosion depends on several factors such as climate, soil type, topography, cropping and land management practices, the antecedent conditions and the size of the area under consideration. The present study was carried out in the lateritic terrain of KCAET campus, Tavanur, Malappuram District. This study was aimed at developing a rainfall simulator and studying the performance of the developed rainfall simulator, the effect of rainfall on soil loss, the effect of rainfall on runoff and developing a soil erosion model. A rainfall simulator was fabricated to study the erosion processes. Rainbird 12115118 Van Pop up sprinkler heads were used as the drop formers. The simulator evaluated for its performance. The soil was reddish brown and belonged to the textural class of sandy loam. It belonged to the Naduvattom series. The experimental set up consisted of three units viz., the runoff plot, the rainfall simulator and the runoff-sediment collection unit. Twelve runoff plots with twelve different slopes of 1.5, 2.0, 2.6, 3.0, 3.2, 4.0, 5.0, 6.0, 9.0, 10, 12 and 13 per cent in different locations, each plot with a size of2 x 1.5 m were prepared. The fabricated rainfall simulator could produce rainfall intensities varying from 8.16 to 8.80 ern/h. The uniformity of rainfall varied from 89.01 to 92.70 per cent and the average drop size varied from 1.5 to 2.8 mm. A relationship between supply pressure and intensity of rainfall as well as intensity and uniformity of rainfall was developed. Studies were conducted on soil loss and runoff at different land slopes under simulated rainfall conditions. The soil loss and runoff was found to increase with increase in rainfall intensity and land slopes and there were no much variations on runoff and soil loss at 6 to 10 per cent land slopes.